Study of Diatoms Epiphytic as Indicators Water Environment Kampar River Around Buluh Cina Village Siak Hulu district of Kampar Regency in Riau Province - Siregar, Sofyan Husein (Jurnal Kajian Lingkungan, 2013)
The research aims to assess the environmental condition of the Kampar River waters based on the species and abundance of epiphytic diatoms, to know the species of epiphytic diatoms seen from water quality condition of Kampar River water sand to determine the dominant species of epiphytic diatoms. The research was conducted on February to March 2013 inthe Kampar River village of Buluh Cina. The method used was a survey method. Analysis and identification at laboratory of Aquatic Ecology Management of Waters Environment, Water Resource Management Department, Faculty of Fisheries and Marine Sciences University of Riau.The results of research were obtained the species and abundance of epiphytic diatoms as many as6 generas with to talabundance (cell/cm26870), of the value of diversity index (H) ranged (0.9312 to 1.8292), the value ofthe diversity index(E) ranged (from 0.1411 to 0.3328), and the dominance index (C) ranged (0.2868 to 0.6797). The results of measurements of water quality parameters of physics and chemistry in the waters of Kampar River Village of Buluh Cina: the temperature ranged from 28 to 310C, the brightness ranged from 40 to 106 cm, turbidity ranged from 5 to 17 NTU, flow velocity ranged from 3.5 to 12 cm/sec, dissolved oxygen ranged from 6 to 6.8 mg/l, pH ranged from 5.32 to 7.8, nitrate ranged from 0.06 to 0.08 mg/l, phosphate ranged from 0.01 to 0.07 mg/l. In general, waters quality condition of Kampar River Villageof Buluh Cina is still in good condition and support for living organisms, especially epiphytic diatoms. Species of epiphytic diatoms that dominate the waters of Kampar River is Nitzchia sp.Keywords: Epiphytic Diatoms, Tolerance Limits, Kampar River.